Perceptions of content marketing : case study on Finnish companies - Hänninen, Heli (2015)
The discipline of marketing has gone through some major changes over the past couple of decades. The power is moving away from companies to consumers, who are playing a more significant role than ever before. Furthermore, the increasing number of marketing channels and the digitalization of media create not only challenges but also opportunities for companies. These shifts in the environment have actually made content marketing to be one of the most popular concepts in marketing today. Content marketing is by no means a new concept, but the recent digital tools in marketing have changed the concept and made it more popular among marketers around the world. Content marketing is and has been a very hot topic in recent years, yet it has achieved relatively little academic attention. Therefore, this study attempts to find out, what does content marketing mean and how it is actually done. This research also aims to contribute some ideas and opinions on what the future of content marketing will hold. Due to the nature of the topic, the research is conducted as a qualitative case study. An abductive approach is taken, in order to refine the existing literature and intertwine this current knowledge with empirical data. Hence, three background interviews with marketing agency professionals were first conducted in order to find out what information is missing and needed in the field of content marketing. Moreover, eight Finnish companies were examined in the light of their content marketing practices to enlighten the literature of content marketing in terms of definitions, processes and future. The results of the study revealed that the definition of content marketing depends on the perspective of the person who defines it. However, based on the results of this research, content marketing is seen as marketing communications that provides valuable and helpful information to a clearly defined target audience with the aim to increase sales. In addition, the process of practicing content marketing appears to be more a continuous cycle than a clear linear line. The future of content marketing was seen differently in the case companies, yet all the interviewees agreed that the importance of content marketing will remain and might even increase in the future.